1978
DOI: 10.1007/bf00379730
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the operators of bacteriophage lambda

Abstract: Oc mutations in the operators of bacteriophage lambda have been used to analyze the functional organization of the operators. In each operator, repressor binding sites 1 and 2, as identified biochemically, were found to be primarily responsible for the repressor affinity of the operators in vitro and for the repression of lytic functions in vivo. In addition, both sites were shown to be involved in the action of cro product at the operators. The data obtained have been used to estimate the repressor affinities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Repressor and Cro respond differently to operator mutations (refs. [14][15][16] and unpublished data), and our experiments indicate that the arm is responsible for this difference in at least three cases. Two of these operator mutations affect base pairs not contacted by the arm (6), yet the arm is partly responsible for their effect on repressor binding.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Repressor and Cro respond differently to operator mutations (refs. [14][15][16] and unpublished data), and our experiments indicate that the arm is responsible for this difference in at least three cases. Two of these operator mutations affect base pairs not contacted by the arm (6), yet the arm is partly responsible for their effect on repressor binding.…”
mentioning
confidence: 58%
“…Plasmids carrying the initiation codon in the same reading frame as the cI gene conferred immunity to XcI7 and/or directed the production of a large amount of a 26,000-dalton protein. Restriction (14) were from this lab's strain collection.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the predicted functions of these regions of the wEf11 genome, and to develop a potentially useful agent for phage therapy, we wished to determine whether deletion or replacement of these sites in phage wEf11 would result in a derivative virus with virulent rather than temperate properties. There is substantial precedent for temperate to virulent conversion of phage by modification of these genomic sites (Bailone & Devoret, 1978;Flashman, 1978;Donnelly-Wu et al, 1993;Bruttin & Brüssow, 1996;Ford et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The classical vir mutants were selected as variants that form plaques on a lawn formed by a lysogen (23). Later studies demonstrated that two mutations in O R and one mutation in O L , or one mutation in O R and two mutations in O L , are necessary and sufficient for virulence (12).…”
Section: Isolation Of Virulent Mutantsmentioning
confidence: 99%